Pemodelan Sistem Monitoring dan Kontrol Kadar Gas Amonia pada Kandang Ayam sebagai Upaya Meningkatkan Kesehatan dan Kualitas - Wakidah, Riska Nur; Haq, Siti Zaenab Nurul; Andrianto, Yeremia Agus; Damayanti, Annisa Maulidia (Jurnal Teknik Elektro Indonesia, 2024)
The success of a broiler chicken business is determined by the harvest results obtained. A good cage and chicken care system can maximize the harvest that will be obtained. The ideal chicken coop is one that has air quality, temperature and humidity that comply with the provisions. Detecting levels of ammonia gas and other gases that are harmful to chickens can be done using an air quality detector. However, what is becoming an obstacle for breeders is that the price of the detector equipment is quite expensive. So a more economical and efficient ammonia gas detection system is needed. In this research, a system for detecting temperature, humidity and ammonia gas levels was created which can be monitored remotely. This research starts from analysis, design, implementation and continues with evaluation. From the research results it was found that the control system can work well, if the ammonia gas level is high then the blower will be ON, and if the ammonia gas has reached the ideal value then the blower will be Off. And when the cage temperature is lower than specified, the incandescent lamp will be on, and vice versa. Apart from that, measured parameters can be displayed on the IoT (Internet of Things) system so that it can increase the efficiency of farmer performance.